Effect of Pesticide Inoculation, Duration of Composting, and Degradation Time on the Content of Compost Fatty Acids, Quantified Using Two Methods - Cardinali, Alessandra (American Society for Microbiology (ASM), 2010)
Compost biobeds can promote biodegradation of pesticides. The microbial community structure changes during the composting process, and simple methods can potentially be used to follow these changes. In this study the microbial identification (MIDI) and ester-linked (EL) procedures were used to determine the composition of fatty acid methyl esters (FAMEs) in composts aged 3 and 12 months, inoculated with 3 recalcitrant pesticides (azoxystrobin, chlorotoluron, and epoxyconazole and a coapplication of all three) after 0, 56, and 125 days of degradation. Pesticide persistence was high, and after 125 days the residue was 22 to 70% of the applied amount depending mostly on the composting age. Seventy-one FAMEs belonging to nine groups were detected. The EL method provided three times as many detections as did the MIDI method and was more sensitive for all FAME groups except alcohol. Thirty-six and five FAMEs were unique to the EL and MIDI methods, respectively. The extraction method was of importance. The EL method provided a higher number of detections for 57 FAMEs, and the MIDI method provided a higher number for 9 FAMEs, while the two methods were equal for 5 FAMEs; thus, the EL method provided a more uniform overall FAME profile. Effects of the other factors were not always clear. Inoculation with pesticide did not influence the FAME profile with the MIDI method, while it influenced cyclopropane and monounsaturated content with the EL method. Composting age and degradation time had an effect on some groups of FAMEs, and this effect was greater with the EL method. The use of some FAMEs as biomarkers to follow microbial community succession was likely influenced by the type of compost and other factors.